Sensory Profile Evaluation Using the CATA (Check-All-That-Apply) Method: A Case Study on Commercial Dipped Wedang Uwuh - Rifqi, Muhammad; Sakinah, Siti Ismaya; Kusumaningrum, Intan Harnesa (Teknotan: Jurnal Industri Teknologi Pertanian, 2025)
Wedang uwuh is a functional drink commonly made of ginger, sappanwood, cinnamon, clove, and sugar. Wedang uwuh has immunomodulatory properties that can help strengthen the immune system. Making wedang uwuh dip is one of the efforts to make it more appealing and easier to serve. Many MSMEs (Micro, Small, and Medium Enterprises) in Indonesia manufacture wedang uwuh dyes. This study aims to determine the sensory profile of wedang uwuh celup products sold on e-commerce by several producers, to determine the sensory profile of wedang uwuh celup products, and to determine the characteristics preferred by panelists based on the attributes tested by 50 panelists with an age range of 18-60 years, with a ratio of 53% male and 47% female. The techniques employed are FGD (Focus Group Discussion), which is used to determine sensory qualities, and CATA (Check-All-That-Apply), which is used to create sensory profiles. The test results revealed a total of 12 sensory attributes, including bright red color, orange-brown color, herbal aroma, ginger aroma, sweet taste, bland taste, bitter taste, spicy sensation, warm sensation, warm afterfeel, bitter aftertaste, and spicy aftertaste. According to the test results, sample code 160 is the most preferred wedang uwuh sample because it is considered ideal by the panelists, namely having a ginger aroma, warm taste, warm feeling after drinking, brownish orange color, and spicy taste after drinking.